Analysis of Appropriate Technology Implementation in Efforts to Increase Rice Paddy Production in Cialam Jaya Village, Konda Sub-district - Muhammad Arifai; Surni; Fahria Nadiryati Sadimantara (International journal of technology and education research, 2025)
This study aims to analyze the efficiency level of the application of appropriate technology in increasing the production of paddy rice in Cialam Jaya Village, Konda District. Population is a generalization area consisting or objects/subjects that have certain quantities and characteristics set by researchers to study and then draw conclusions (Sugiyono, 2016). The population in this study was a group of rice farmers in Cialam Jaya Village, South Konawe Regency, totaling 20 farmers. Data analysis used is regression analysis with the Cobb-Douglas production function model to determine the effect of X on Y, using the Program for Social Science (SPSS). While to determine the level of efficiency in this study we use the Frontier program. technically this study has been fairly efficient where the smallest estimated efficiency value is 0.736 or 73% and for the largest value is 0.958 or 96%. This can be considered efficient if the value is > 0.7 in the form of a percentage of 70%